Report on a workshop on the design and implementation of pastoral development projects for tropical Africa - International Livestock Centre for Africa (1980)
Synthesis of discussion on the design and implementation of pastoral development projects, particularly with reference to the project concept, basic constraints and information needs, organizational aspects and monitoring, w. recommendations.